What do we realize when we don’t see? - Sousa, Joana Belarmino de (2009)
This article answers a key question discussed at the Seminar "To see and not to see", inquiring the nature of tactile perception, specially on born blind people. The argumentation, despite the fact that it is related to some theories, is structured more in an informal language than in a scientific one, bringing to the debate experiences of my own childhood. It is based on a key concept, explored in my PhD thesis, which I defined as "tactile worldseeing" to explain a tactile way of perceiving the world.